The emergence of capitalism in early America - Calvo, Christopher W. (University Press of Florida, 2020)
"Contesting the assumption that early American economists were committed to Adam Smith's ideas of free trade and small government, this book provides a comprehensive history of the nation's economic thought from 1790 to 1860, tracing the development of a uniquely American understanding of capitalism"--